Investigation Of Effects Of Carbon Nanofiber Nanofluid In Drilling Of AISI 304 Stainless Steel - Liew, Pay Jun; Mohd Hajazi, Aini Syahida; Shaaroni, Ainusyafiqah; Sulaiman, Mohd Amri; Raja Abdullah, Raja Izamshah (Penerbit Universiti, UTeM, 2018)
This paper presents the experimental study of the effects of carbon nanofiber (CNF) nanofluid in drilling of AISI 304 stainless steel. The drilling performance was assessed based on the surface roughness inside the holes, hole dimensional accuracy and burr formation using four different CNF nanofluid concentrations. The machining performance of CNF nanofluid also compared with the base fluid (deionized water) only. The experimental results show that the CNF nanofluid not only improve the surface finish and hole accuracy, but also reduce the burr formation at the circumference of the drilled hole.